Modeling the Brazil ?Malvinas Confluence: Model Configuration - Palma, Elbio Daniel; Matano, Ricardo; Piola, Alberto Ricardo
The upper ocean circulation near the western margin of the South Atlantic Ocean is dominated by the southward flow of the warm and salty Brazil Current and the northward flow of the cold and relatively fresh Malvinas Current. The collision, near 38 o S, of the two jets produces a strong frontal zone known as the Brazil-Malvinas Confluence (BMC). The BMC is populated with eddies and meanders and is known to be one of the most energetic areas of the world oceans (Chelton et al) [1] . In this article we describe the numerical strategies used to implement a regional, eddy resolving, three-dimensional numerical model of the BMC. The numerical experiments consisted of integrations using idealized set-ups and experiments with a realistic basin configuration. The experiments in idealized basins were used to test the numerical implementation of open boundary conditions in a dynamical setting that includes both passive and active lateral boundaries. The simulations in a realistic basin ere forced with climatological wind stress and heat fluxes at the surface and mass and heat fluxes extracted from global simulations across the lateral boundaries. The numerical results so obtained appear to reproduce the general features observed in hydrographic and remote sensed data, including the observed mean position of the BMC and volume transports of the boundary currents, and the development of warm intrusion eddies. Fil: Palma, Elbio Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur. Departamento de Física; Argentina Fil: Matano, Ricardo. State University of Oregon; Estados Unidos Fil: Piola, Alberto Ricardo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmósfera y los Océanos; Argentina